APROXIMAÇÕES ENTRE OS REGISTROS DE REPRESENTAÇÃO SEMIÓTICA E A DISCALCULIA: uma revisão bibliográfica no ensino de matemática - DINIZ, Cristiane Araujo (2023)
Dyscalculia is a learning disorder that impacts the ability to think, assess, and reason through mathematical processes, significantly affecting an individual's daily and social life. This dissertation explored effective strategies based on the Theory of Semiotic Representation Registers (TRRS) for students with dyscalculia in the later years of elementary school, aiming to enhance the understanding and application of mathematical concepts. Structured as a systematic literature review, it employed Content Analysis as the analytical method. The research aimed not only to deepen knowledge on the topic but also to provide practical guidelines to help students with dyscalculia overcome their challenges and achieve better academic performance in mathematics. Using Bardin's content analysis and a systematic review of the literature on dyscalculia to identify, evaluate, and synthesize effective TRRS strategies, the study emphasized the need for adaptive pedagogical strategies, addressing the lack of studies in the area and proposing directions for future research. Key findings highlighted the need for adaptive and personalized pedagogical approaches, incorporating technology and manipulative materials. The importance of inclusion and adaptation in contemporary education was discussed, emphasizing teachers' roles in promoting a more equitable society. It underscored the necessity of understanding and addressing specific learning disorders to ensure all students have equal access to education, thereby reinforcing the significance of continuous teacher training and the integration of multidisciplinary approaches to foster a more inclusive and accessible educational environment, and its crucial mission in building a fairer society.